10.1016/s1541-9800(05)70709-2 (CrossRef Listing of Deleted DOIs, 2000)
In July 2025, the Food and Drug Administration (FDA) warned of significant weight loss among young children receiving stimulants for attention-deficit hyperactivity disorder. However, real-world evidence on the magnitude and prevalence of stimulant-associated weight loss remains limited. This study evaluated short-term weight changes after methylphenidate initiation among youth aged 3-18 years using the Medical record Observation and Assessment of drug safety Common Data Model (MOA CDM) in Korea. We conducted a retrospective study using electronic health record-based MOA CDM data from January 2008 to December 2024. The cohort included individuals aged 3-18 years with at least one methylphenidate prescription and had available weight measurements. The index date was defined as the first prescription date. Individuals without weight data within 45 days before or 90 days after the index date were excluded. Outcomes included changes in body weight (kg) and weight percentile, and the proportion having a ≥ 10-percentile decline. Weight percentiles were calculated using the 2017 Korean National Growth Charts for Children and Adolescents. A total of 2087 youths from 17 nationwide hospitals were included; 68.71% were male, and 58.12% were aged 6-10 years. Within 3 months, mean body weight decreased by -0.33 kg (95% confidence interval [CI], -0.44 to -0.22) and mean weight percentile decreased by -2.49 percentiles (95% CI, -2.83 to -2.15). Overall, 21.57% had a ≥ 10 percentile decline, with larger reductions among pre-school-aged children (28.57%). Our findings underscores the importance of growth monitoring during treatment initiation.